Review of Economics and Statistics 2022 Annual Report (The Review of Economics and Statistics, 2022)
Current Editorial Board:Pierre Azoulay, Massachusetts Institute of TechnologyOlivier Coibion, University of Texas, AustinWill Dobbie (Co-Chair), Harvard UniversityRaymond Fisman (Co-Chair), Boston UniversityBenjamin R. Handel, University of California, BerkeleyBrian A. Jacob, University of MichiganKareen Rozen, Brown UniversityXiaoxia Shi, University of Wisconsin–MadisonTavneet Suri, MITDaniel Xu, Duke UniversityRecently Retired from the Editorial Board:Rema N. Hanna (Co-Chair), Harvard UniversityShachar Kariv, University of California, BerkeleyTable 1—Manuscripts Submitted and Published, 2017–2021This table shows the trends in papers submitted and published over the past five years. The journal has seen increased growth in paper submissions: 14% in 2018, 11% in 2019, and 25% in 2020. Submission numbers remained steady in 2021. The number of published papers has remained steady, ranging from 65 to 70 papers per year.Table 2—Status of Manuscripts by Year of Submission, 2017–2021This table shows the status of manuscripts submitted over the past five years. The papers summarily rejected remained steady, ranging from 54% to 62% of papers submitted. The percent of papers sent out for review but ultimately rejected has remained steady, ranging from 29% to 35% of papers. Acceptance rates range from 7% to 8% of papers submitted. Papers submitted in 2021 have not had enough time to accurately reflect the acceptance rate.Table 3—Decision Time for Manuscripts Sent to Referees for ReviewThis table reports the decision time for manuscripts sent to referees for review over the past five years. In 2018, the average decision time for papers that were sent to referees was 95 days. The average decision time in 2021 improved to 86 days. In addition, the decision time at the right tail improved substantially.Table 4—Distribution of First Decision Times by Submission YearThis table includes all first-round paper submissions and shows the distribution of decision times in monthly increments for the past five years. This table also reflects the improvement in the journal's decision turnaround times. In 2021, 86% of manuscripts received a decision within three months and 99% within five months.Table 5—Subject Matter of Published Manuscripts, 2021This table shows the distribution of the subject matter of papers published in 2021. Published papers covered a variety of subjects, but the most common were microeconomics and macro- and monetary economics. Table 1.Manuscripts Submitted and Published, 2017–2021YearSubmittedPublished20171,0496820181,2007020191,3306620201,6666520211,67465